Italian regions turn fifty. A new typology of regional party systems in Italy, 1970-2020. Issue 4 (2nd October 2021) - Valbruzzi, Marco; Vignati, Rinaldo
ABSTRACT: The article analyses the transformations of the regional party systems that have occurred since the first elections held in 1970. In particular, after a preliminary analysis of the massive changes observed in the electoral arena before and after the 1995 turning point, the article discusses existing typologies of Italian regions and suggests a new analytical framework that accounts for the transformations that have occurred at the regional level in the last three decades. The second part of the paper analyses the most recent series of regional elections (2018–20) and focuses specifically on the changing structure of inter-party competition and the re-emergence of a bipolar dynamic of competition between 'fragmented' coalitions, in contrast with the trend observed at the national level.